Preparation of High-Temperature-Resistant Polybenzoxazole Paper by a Two-Step Method - Wanli Zhou; Xinye He; Kuan Yang; Heng Wang; Yizi Chen; Song Wang; Qinglan Xue (Advances in Polymer Technology)
Polybenzoxazole (PBO) paper, made of PBO chopped fibers and PBO fibrids, is used in many cutting-edge fields because of its excellent properties. The rigid molecular structure makes PBO only dissolved in strong acids such as fuming sulfuric acid and polyphosphoric acid at a very high temperature. Due to the harsh preparation conditions, it is not easy to industrialize PBO fibrids. Herein, a two-step method was used to prepare the PBO paper. Firstly, polyhydroxyamide (PHA) was synthesized in an organic solvent and used to prepare fibrids, and the PHA paper was then prepared using PHA fibrids with a traditional wet papermaking process, and the obtained PHA paper was further converted into PBO paper by thermal cyclization. The results show that the PHA fibrids have a high length–diameter ratio, film shape, and abundant hair structure, and the tensile index of the PHA base paper is as high as 123.3 N·m/g. After thermal cyclization, the structure and morphology of the paper have little change, and the mechanical properties of the paper have a certain loss. However, it is still much higher than that of PBO paper prepared directly from PBO fibrids and has excellent thermal stability, so it is suitable for preparing high-temperature-resistant paper-based composites.